1994
DOI: 10.1002/ajmg.1320510444
|View full text |Cite
|
Sign up to set email alerts
|

Mosaicism in fragile X affected males

Abstract: Fragile X affected males have an expansion of a CGG repeat and a hypermethylated CpG island 5' to the FMR-1 gene. Mosaic males with both a premutation and full mutation have been noted among the affected individuals. Such mosaic males are most easily identified by the presence of a methylated restriction fragment characteristic of the full mutation and an additional unmethylated fragment in the premutation range in Southern analyses with EcoR I and the methylation-sensitive enzyme Eag I and a probe such as StB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
133
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 147 publications
(141 citation statements)
references
References 13 publications
7
133
1
Order By: Relevance
“…10 The instability is associated with unmethylated CGG repeats while large also as the stable allele with 26 repeats is detected in the transgenic mice along with alleles with expanded CGG repeats as seen in several human patients. [28][29][30][31] It remains to be seen if stability and methylation are correlated in these transgenic mice. In an earlier report in human patients mosiacism in repeat number was correlated with the absence of DNA methylation.…”
Section: Discussionmentioning
confidence: 99%
“…10 The instability is associated with unmethylated CGG repeats while large also as the stable allele with 26 repeats is detected in the transgenic mice along with alleles with expanded CGG repeats as seen in several human patients. [28][29][30][31] It remains to be seen if stability and methylation are correlated in these transgenic mice. In an earlier report in human patients mosiacism in repeat number was correlated with the absence of DNA methylation.…”
Section: Discussionmentioning
confidence: 99%
“…A minority of individuals with FXS have a mosaic pattern with some cells showing sizes of less than 200 repeats and partially active gene expression . Methylation mosaicism has also been shown in affected individuals such that a full mutation shows only partial methylation (Nolin et al, 1994). It has been known that mosaicism is correlated with a less severe phenotype and a better prognosis of this disorder (McConkie-Rosell et al, 1993;Cohen et al, 1996).…”
Section: The Molecular Biology Of the Fragile X Syndrome (Fxs)mentioning
confidence: 99%
“…For example, the brothers of males with full mutations are less likely to be affected than the sons of their daughters. Furthermore, it has been shown that there is a strong familial clustering of repeat size expansion such that the offspring of some female carriers tend to have the full mutation, whereas those of other female carriers tend to be only premutations (Nolin et al, 1994(Nolin et al, , 1996. Individuals with fewer than 60 repeats have never been found to have had affected male children.…”
mentioning
confidence: 99%
“…In female patients, X-inactivation silences either the mutant or normal X chromosome in each cell, resulting in mosaic FMRP expression, with variable skewing of X inactivation leading to variability in the percentage of cells expressing FMRP (MartĂ­nez et al, 2005). In addition, variable silencing of the FMR1 gene in different cells, can results in mosaic expression of FMRP in some male patients (Pieretti et al, 1991;Nolin et al, 1994;Rousseau et al, 1994).…”
Section: Introductionmentioning
confidence: 99%